The Anatomical and Physiological Basis of Clinical Tests of Otolith Function. A Tribute to Yoshio Uchino - Curthoys, Ian S. (Frontiers in Neurology, 2020)
Otolithic receptors are stimulated by gravitoinertial force (GIF) acting on the otoconia resulting in deflections of the hair bundles of otolithic receptor hair cells. The GIF is the sum of gravitational force and the inertial force due to linear acceleration. The usual clinical and experimental tests of otolith function have used GIFs (roll tilts re gravity or linear accelerations) as test stimuli. However the opposite polarization of receptors across each otolithic macula is puzzling since a GIF directed across the otolith macula will excite receptors on one side of the line of polarity reversal (LPR at the striola) and simultaneously act to silence receptors on the opposite side of the LPR. It would seem the two neural signals from the one otolith macula should cancel. In fact, Uchino showed that instead of cancelling, the simultaneous stimulation of the oppositely polarized hair cells enhances the otolithic response to GIF – both in the saccular macula and the utricular macula For the utricular system there is also commissural inhibitory interaction between the utricular maculae in each ear. The results are that the one GIF stimulus will cause direct excitation of utricular receptors in the activated sector in one ear as well as indirect excitation resulting from the disfacilitation of utricular receptors in the corresponding sector on the opposite labyrinth. There are effectively two complementary parallel otolithic afferent systems – the sustained system concerned with signalling low frequency GIF stimuli such as roll head tilts and the transient system which is activated by sound and vibration (3). Clinical tests of the sustained otolith system - such as ocular counterrolling to roll-tilt or tests using linear translation - do not show unilateral otolithic loss reliably, whereas tests of transient otolith function (vestibular evoked myogenic potentials (VEMPs) to brief sound and vibration stimuli) do show unilateral otolithic loss. The opposing sectors of the maculae also explain the results of galvanic vestibular stimulation (GVS) where bilateral mastoid galvanic stimulation causes ocular torsion position similar to the otolithic response to GIF. However, GVS stimulates canal afferents as well so the eye movement response is complex.